Implementing voluntary assisted dying in Victoria, Australia. (16th February 2021) - O'Connor, Margaret; Mandel, Catherine; Mewett, Greg; Catford DCH, John; McMaugh, Jarrod
Abstract: This paper describes the process undertaken to implement voluntary assisted dying (VAD) in Victoria, Australia. While the Bill became law in December 2017, an 18‐month implementation period was allocated to anticipate the clinical complexities of how VAD would occur in various settings, requiring an exhaustive process to address the significant changes required of health services.Implementation involved detailed health planning, and the process included a large range of health practitioners and community members, keeping a close eye to the complementarity of the various pieces of work, as well as the many safeguards required.Written from the perspective of those involved in planning the implementation, it is hoped that articulating this Victorian experience will assist others. Implementation is a complex process and takes time; it must be broadly collaborative and reflective, to ensure both health professionals and community members understand the legislative changes, as well as the responses required.